1994
DOI: 10.1016/0006-2952(94)90369-7
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of glucose utilization in 3T3 adipocytes and rat diaphragm in vitro by the sulphonylureas, glimepiride and glibenclamide, is correlated with modulations of the cAMP regulatory cascade

Abstract: Abstract--The long-term hypoglycemic activity of sulphonylurea drugs has been attributed, in part at least, to the stimulation of glucose utilization in extra-pancreatic tissues. The novel sulphonylurea, glimepiride, gives rise to a longer lasting reduction in the blood sugar level in dogs and rabbits compared to glibenclamide (Geisen K, Drug Res 38: 1120-1130). This cannot be explained adequately by elevated plasma insulin levels. This study investigated whether this prolonged hypoglycemic phase was based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
6

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 80 publications
1
43
0
6
Order By: Relevance
“…It was documented that, gluconeogenesis and hepatic glucose production were inhibited by sitagliptin in HFD-induced obese rats due to decreased glycerol availability as a result of reduced glycerol release from adipose tissues [22]. Furthermore, studies suggested an insulin sensitizing action of glimepiride possibly by stimulation of GLUT4 transport protein activation and/or translocation in fat and muscle [23].…”
Section: Discussionmentioning
confidence: 99%
“…It was documented that, gluconeogenesis and hepatic glucose production were inhibited by sitagliptin in HFD-induced obese rats due to decreased glycerol availability as a result of reduced glycerol release from adipose tissues [22]. Furthermore, studies suggested an insulin sensitizing action of glimepiride possibly by stimulation of GLUT4 transport protein activation and/or translocation in fat and muscle [23].…”
Section: Discussionmentioning
confidence: 99%
“…]glucose (300 mCi/mmol, DuPont NEN) into glycogen (28,29). 0.5 ml of adipocytes in KRH were diluted with 0.5 ml of KRH and incubated in the absence or presence of insulin in a shaking water bath under an atmosphere of 5% CO 2 for 20 min at 37°C.…”
mentioning
confidence: 99%
“…More importantly, other studies revealed that glimepiride not only stimulates cAMP-PDE but also decreases protein kinase A (PKA) activity, possibly due to reduced intracellular cAMP concentration. [25,26] These results indicate that glimepiride decreases cytosolic cAMP levels via the regulation of cAMP-PDE and PKA. Furthermore, insulin has been reported to reduce cytosolic cAMP level by activating cAMP-PDE [27][28][29] and inhibiting adenylcyclase synthesis.…”
Section: Tcpmentioning
confidence: 79%